The Investigation of Using Out-Classroom Experiences to Enhance Indonesian EFL Learners’ Speaking Performance - Ezis Japar Sidik; Dhafid Wahyu Utomo; Yudi Juniardi (English Education Department at FKIP Nommensen University, 2021)
The role of English in Indonesia can be said quite special because English is the only compulsory foreign language included in secondary curriculums. However, the special status of English in national education is not accompanied by satisfactory results. Out-classroom experience (OCE) is believed to overcome this issue and has been applied successfully. Therefore, this study investigates the use of out-classroom experience in enhancing Indonesian EFL learners’ ability in speaking English. By conducting a case study approach, the research used triangulation data collection techniques consisting of classroom observation, interview, and speaking performance test. The study involved 40 undergraduate students from one of the public universities in Banten province as its subjects. The result showed that the use of OCE positively contributes to the development of students’ speaking development. Out-classroom activities can facilitate the learners to access or even create language exposures by themselves. This study provided some implications about using OCE for language teachers and educational practitioners. Keywords: Out-Classroom experiences, speaking, college students, EFL context